Acute health problems due to recreational drug use in patients presenting to an urban emergency department in Switzerland (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: To describe acute toxicity of recreational drugs including novel psychoactive substances. METHODS: We included all cases presenting at the emergency department (ED) of the University Hospital of Basel, Switzerland, between October 2013 and September 2014 with acute toxicity due to self-reported recreational drug use or with symptoms/signs consistent with acute toxicity. Isolated ethanol intoxications were excluded. Intoxications were confirmed with immunoassays and liquid chromatography coupled with mass spectrometry (LC-MS/MS), which also detected novel psychoactive substances. RESULTS: Among the 47,767 attendances at the ED, 216 were directly related to acute toxicity of recreational drugs. The mean patient age was 31 years and 69% were male. Analytical drug confirmation was available in 180 cases. Most presentations were related to cocaine (36%), cannabis (31%), opioids (13%), 3,4-methylenedioxy-methamphetamine (MDMA, 9%), other amphetamines (7%), benzodiazepines (7%), and lysergic acid diethylamide (LSD, 5%). The substances most commonly detected analytically were cannabis (37%), cocaine (33%), opioids (29%), benzodiazepines (21%), and amphetamines including MDMA (13%). Notably, there were only two cases of novel psychoactive substances (2,5-dimethoxy-4-bromophenethylamine [2C-B] and pentylone). The most frequent symptoms were tachycardia (31%), anxiety (27%), nausea or vomiting (23%), and agitation (22%). Severe complications included myocardial infarction (2), psychosis (10), seizures (10), and 1 fatality. Most patients were discharged home (68%), 8% were admitted to intensive care and 9% were referred to psychiatric care. CONCLUSION: Medical problems related to illicit drugs mostly concerned cocaine and cannabis and mainly involved sympathomimetic toxicity and/or psychiatric disorders. ED presentations associated with novel psychoactive substances appeared to be relatively rare.